The Risk-free rate in a finite horizon model with bequest - Xiaoyong Cui; Liutang Gong (Bulletin of Economic Research, 2012)
This paper studies the risk‐free rate in an overlapping generations economy with bequests. It is shown that the risk‐free rate depends on risk aversion, the elasticity of intertemporal substitution, the share of wealth invested in human wealth, life expectancy, and the preference for bequests. In a standard life‐cycle context, mortality increases the subjective time rate of discount, and thus increases the compensation required to postpone consumption. This latter effect is offset in a bequest‐driven model of the type considered here, leading to much more powerful income effects. In this sense, the model provides a bequest‐motive explanation for the risk‐free rate puzzle put forward by Weil in 1989.